ENGLISH INSTRUCTIONS MEDIA BOOK IN IMPROVING ENGLISH OF ELEMENTARY SCHOOL TEACHERS IN TANGERANG - Euis Yanah Mulyanah; Ishak Ishak (JPSD (Jurnal Pendidikan Sekolah Dasar), 2020)
AbstractThis research was conducted to improve the teachers' English mastery, especially in elementary school teachers in Tangerang, Indonesia. The method of this research was a quantitative approach with a quasi-experimental design by using nonequivalent control group design (pretest-posttest), to compare the English skill levels before and after treatment through the English Instructions book. The researcher took samples of 40 teachers from several Elementary School teachers in Tangerang. The result of the research found that the average post-test score of the experimental group was 88.06 and the average post-test score of the control group was 79.40, which means that there was an increased score of 8.65 or 11%. The hypothesis of the research stated that H0 was rejected and Ha was accepted, it means that there were significant changes in improving the teachers' English skill of Elementary School using the English instructions book.Keywords: English Instructions Book, Elementary School